The Relationship Between Full-Range Leadership and Employee Engagement Among Bank Employees at Selected Banks in Malaysia - Alifah Ilyana Zamri,; Nor Hazana Abdullah, (Research in Management of Technology and Business, 2024)
Full-range leadership approaches have emerged and been used because of the changing nature of the workplace and the requirement to effectively manage either face-to-face or the distant teams. Full-range leadership practices by the leaders can be impactful towards employee engagement in an orgenization. Quantitative methods have been employed as the research methods along with the questionnaires that had been distributed among 400 bank employees at the selected banks in Malaysia. The research focuses on the selected banks and implement the data collection techniques which is by conducting a survey by handling out the questionnaires to the respondents from the established sources. The obtained data is then analyzed by using Statistical Package for Social Science (SPSS) software in order to determine the strength and nature of the relationship between full-range leadership practices and employee engagement. To summarize,  all findings from the previous published research related to full-range leadership and employee engagement can be considered as part of the contributions for this research in order to provide valuable insights for bank management teams, employee engagement and overall productivity at the selected banks in Malaysia which are RHB, CIMB, Maybank and Bank Islam.